Synthesis and Comparison of Soft-Switched Operating Modes of a Series Resonant Balancing Converter for Bipolar DC Grids - Sachin Yadav; Pavol Bauer; Zian Qin (IEEE Open Journal of the Industrial Electronics Society)
This article discusses the various operating modes of a series resonant balancing converter for bipolar dc grids. It is shown that the converter can be operated in both the capacitive and inductive regions with respect to the resonant frequency of the LC tank. Furthermore, concerning the pulse width modulation signals to the switches, the converter can either be operated by controlling the phase shift between the converter half bridge legs or the duty cycle of the half bridges. A qualitative comparison of the different modes proves that a) the phase shift modes have better soft switching capabilities, b) the capacitive phase shift mode can show zero voltage switching at switch turn-on in the whole operating range, c) the losses in case of capacitive phase shift mode shows best performance at low load power, d) the inductive region power modes show lower rms current for the same power flow compared with capacitive region modes which lead to lower losses at higher output power. The simulation and experimental results depict the operation of all the modes. Finally, a prototype is designed to validate all operating modes, demonstrating $>$ 99% system efficiency at 1.75 kW.